GWAS-based dissection of important grain mineral and anti-nutrient traits in a diverse set of pearl millet germplasm across multi-environments - S. Hemanth; Sumer Pal Singh; Tripti Singhal; Aavula Naveen; Sunaina Yadav; Chandan Kapoor; Satyam Sharma; H.A. Bhargavi; Thippeswamy Danakumara; David Jesse Jangala; Nirupma Singh; T. Nepolean; et al. (Journal of Cereal Science, 2026)

Genetic Variability and Diversity Analysis for Nutritional and Anti-nutritional Traits in Pearl Millet [Pennisetum glaucum (L.) R.Br] - Tripti Singhal; S. P. Singh; Sunaina Yadav; Naveen Aavula; Chandan Kapoor; Nirupma Singh; C. Tara Satyavathi (Biochemical Genetics, 2026)

Comprehensive assessment of low-rancid, high-performing pearl millet genotypes in a global germplasm collection using multi-trait stability indices - H.A. Bhargavi; Sumer Pal Singh; Suneha Goswami; Naveen Aavula; Sunaina Yadav; S. Hemanth; Tripti Singhal; Thippeswamy Danakumara; P. Shashikumara; Chandan Kapoor; Nirupma Singh; C. Tara Satyavathi (Journal of Cereal Science, 2026)

Identification of High-Performing and Stable Pearl Millet Genotypes Using Multi-trait Stability Index - Tripti Singhal; C. Tara Satyavathi; S. P. Singh; Mukesh Sankar; Sunaina Yadav; M. Mallik; C. Bharadwaj (Agricultural Research, 2026)

Multi-trait ideotype-based selection and stability analysis in pearl millet minicore collection for diverse production environments - Chandan Kapoor; Anamika; Sumer Pal Singh; Sudhir Kumar; S. Mukesh Sankar; Nirupma Singh; Tripti Singhal; Naveen Aavula; S. Hemanth; Vikas Khandelwal; V. Chinnusamy (Euphytica, 2026)

Nutrient dynamics in pearl millet: Impact of seed soaking on minerals and anti-nutrient contents - Hemanth S; Sumer Pal Singh; Tripti Singhal; Sunaina Yadav; Chandan Kapoor; Aavula Naveen; H.A. Bhargavi; Satyam; Anamika; Nirupma Singh; M.C. Meena; Ashok Kumar; et al. (Journal of Cereal Science, 2025)

Functional characterization of the replication-associated protein (Rep) promoter of an alpha-satellite associated with Ageratum enation virus - Tripti Singhal; Taruna Gupta; Sunny Dhir; Jitendra Kumar; Vanita Chandel; Ashish Srivastava (Phytoparasitica, 2025)
Ageratum enation virus (AEV) ( Begomovirus agerati) , belonging to the genus Begomovirus , is associated with DNA components known as alphasatellite and betasatellites. The alphasatellite encodes the replication-associated protein (alpha-Rep), which is essential for self-replication but relies on helper viruses for transmission between plants. In this study, we propose that the alpha-Rep promoter exhibits bidirectional promoter activity and can drive the expression of heterologous genes in plants. Using Agrobacterium-mediated transient and stable transgenic techniques, we identified the minimal promoter sequence of the Rep gene from the Ageratum enation virus-associated alpha satellite (AEA) ( Colecusatellite agerati) that initiates β-glucuronidase (GUS) reporter gene transcription in Nicotiana benthamiana plants. Promoter deletion analysis showed varying promoter activities. Especially, all essential cis-elements for strong promoter activity were located within the 331 nucleotides upstream of the translation start codon, displaying robust and consistent transient GUS expression compared to the control promoter (CaMV35S). The findings lay the groundwork for developing a versatile viral vector system suitable for reverse genetics and genome editing across a broad host range, enhancing our understanding of viral-host interactions and their applications in biotechnology.

Delineation of selection efficiency and coincidence of multi-trait-based models in a global germplasm collection of pearl millet for a comprehensive assessment of stability and high performing genotypes - Aavula Naveen; Sumer Pal Singh; Tripti Singhal; Sanjana Reddy; H. A. Bhargavi; Sunaina Yadav; Hemanth S; Chandan Kapoor; Patel Supriya; Nirupma Singh; C. Tara Satyavathi (Genetic Resources and Crop Evolution, 2025)

Foliar blast and seedling dehydration stress tolerance in wild Pennisetum monodii germplasm and trait variability in interspecific crosses with Pennisetum glaucum - Chandan Kapoor; Anamika; Sumer Pal Singh; S. Mukesh Sankar; G. Prakash; Sudhir Kumar; Nirupma Singh; H. A. Bhargavi; Tripti Singhal (Genetic Resources and Crop Evolution, 2025)

Hydroponics mediated seedling dehydration stress revealed variable tolerance in pearl millet (Pennisetum glaucum L.) minicore collection - Chandan Kapoor; Anamika; Sumer Pal Singh; Sudhir Kumar; S. Mukesh Sankar; Nirupma Singh; Tripti Singhal (Genetic Resources and Crop Evolution, 2025)

Inheritance and molecular mapping of gene controlling cream grain color in pearl millet [Pennisetum glaucum (L.) R. Br.] - Sunaina Yadav; S. P. Singh; Tripti Singhal; S. Mukesh Sankar; H. A. Bhargavi; Naveen Aavula; C. Tara Satyavathi (Euphytica, 2023)

Genetic elucidations of grain iron, zinc and agronomic traits by generation mean analysis in pearl millet [Pennisetum glaucum (L.) R. Br.] - Sunaina Yadav; S.P. Singh; Tripti Singhal; Mukesh Sankar S; Singh Anju-Mahendru; Bhargavi H.A; Naveen Aavula; Sonu; Suneha Goswami; C. Tara Satyavathi (Journal of Cereal Science, 2023)

Achieving nutritional security in India through iron and zinc biofortification in pearl millet (Pennisetum glaucum (L.) R. Br.) - Tripti Singhal; C. Tara Satyavathi; S. P. Singh; M. Mallik; N. Anuradha; S. Mukesh Sankar; C. Bharadwaj; Nirupma Singh (Physiology and Molecular Biology of Plants, 2022)